Cannabis use and the risk of anxiety and depression in women: A comparison of three Swedish cohorts. (1st November 2020) - Rabiee, Rynaz; Lundin, Andreas; Agardh, Emilie; Hensing, Gunnel; Allebeck, Peter; Danielsson, Anna-Karin
Highlights: We studied 1 100 women in cohorts from different time periods. We explored links between cannabis use, period of use, anxiety & depression. Cannabis during the 1970's and 1980's was associated with depression. Cannabis during the 2000's was associated with both anxiety and depression. The link between cannabis and depression was clearer in the 2000's than in prior years. Abstract: Background: The associations between cannabis use and anxiety or depression remain unclear. If cannabis affects these conditions, it is of interest to examine possible changes in cannabis use over time, in relation to anxiety and depression, as cannabis potency has increased in recent decades. Methods: Cohorts from the Women and Alcohol in Gothenburg study (n = 1 100), from three time periods were used to examine associations over time between cannabis use and anxiety and depression. Logistic regression analyses were used and relative excess risk due to interaction (RERI) was calculated to examine potential additive interactions between period of cannabis use, cannabis use, and anxiety or depression. Findings: Cannabis use was associated with anxiety in the oldest cohort (examined 1986–1992, born 1955/65), OR = 5.14 (1.67–15.80, 95 % CI), and with both anxiety and depression in the youngest cohort (examined 2000–2015, born 1980/93), OR = 1.66 (1.00–2.74, 95 % CI) and 2.37 (1.45–3.86, 95 % CI), respectively. RERI was significant between cannabis use and depression in the youngest cohort when compared with older cohorts (1.68 (0.45–2.92, 95 % CI)). Limitations: Cross-sectional data prevent statements on causality, though between-cohort comparisons are possible. Conclusion: The association between cannabis use and depression becomes more pronounced when adding the effect of period of use rather than looking at the effect of cannabis use itself. This study provides clinicians and public health workers with scientifically underpinned knowledge regarding the link between cannabis use and depression, of particular importance given increasing cannabis potency.